Fragile X syndrome is less common than previously estimated. Issue 1 (January 1997) - Morton, J E; Bundey, S; Webb, T P; MacDonald, F; Rindl, P M; Bullock, S
Abstract : In 1986, a population study of school children in the city of Coventry gave an overall prevalence in males and females for fragile X syndrome of 1/952. The 29 children diagnosed as having fragile X syndrome in this study have been re-evaluated with molecular diagnostic techniques. Eighteen of the original 29 children have been found not to have the expansion of the FMR1 gene associated with fragile X syndrome. Revised prevalence figures have been calculated giving rise to an overall prevalence figure of 1/2720 (range 1/2198-1/3089). If the four children lost to follow up are also assumed not to have the fragile X syndrome, the revised prevalence figure was 1/5714 (range 1/4762-1/6349). Clinical review of boys with severe mental retardation from this and a subsidiary study show that the clinical features of head circumference greater than the 50th centile, testicular volume greater than the 50th centile, and IQ between 35 and 70 remain helpful in distinguishing boys with fragile X syndrome from those who have non-specific mental retardation.